Diagnóstico de conservação preventiva como ferramenta de proteção ao patrimônio móvel: estudo de caso da coleção de Etnografia Curt Nimuendajú - FONSECA, Ana Paula Souza (2019)
The research is a case study developed at Curt Niumendajú ethnographic reserve, from Emilio Goeldi Pará Museum, and it had as a goal to propose a basic diagnostic of Preventive Conservation. In order to present an overview of degradation agents, forms of packaging and the dynamics within the reserve, always considering the cooling system of high temperatures and low humidity installed in the technical reserve, the research aims to contribute to the general state of the acquis documentation after theimplementation of this system. To obtain this purpose, the monitoring of temperature and humidity in macroclimates and microclimates were conducted, aiming to understand: 1)the parameters on which the collection is kept daily; 2) the materials used for packaging of parts and 3) the hygiene practices. The results showed that the acquis, despite havingtemperature humidity index not always consistent with the literature, remains generally on a steady state, with problems at certain points and pieces. These results require further analysis for the accurate determination of the causative agent of the damage. With regard to hygiene, small changes in the frequency and method of cleaning the space andfurniture would result in major changes to the conservation of the collection, once the presence of certain pests (arthropods) was identified. These pests in turn also need to be identified in the future in order to define how dangerous their presence is at the local. So, despite the initial diagnosis developed for the collection, this shows that the general conditions are positive requiring more investments in the conservation area, whether in research and in labor, so that the Goeldi Museum continues adequately fulfilling its role oftrustee for this heritage that belongs to all Amazonian communities.